2019
DOI: 10.1002/bjs.11093
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre study of multidisciplinary team assessment of pancreatic cancer resectability and treatment allocation

Abstract: Background: Multidisciplinary team (MDT) meetings have been adopted widely to ensure optimal treatment for patients with cancer. Agreements in tumour staging, resectability assessments and treatment allocation between different MDTs were assessed.Methods: Of all patients referred to one hospital, 19 patients considered to have non-metastatic pancreatic cancer for evaluation were selected randomly for a multicentre study of MDT decisions in seven units across Northern Europe. Anonymized clinical information and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 22 publications
2
50
0
1
Order By: Relevance
“…We thank Del Chiaro and Schulick for their interest in our recent paper on multidisciplinary team assessments of pancreatic cancer resectability and treatment allocation. We agree that our finding of only 64·1 per cent agreement in resectability assessment in pancreatic cancer patients is concerning.…”
supporting
confidence: 60%
“…We thank Del Chiaro and Schulick for their interest in our recent paper on multidisciplinary team assessments of pancreatic cancer resectability and treatment allocation. We agree that our finding of only 64·1 per cent agreement in resectability assessment in pancreatic cancer patients is concerning.…”
supporting
confidence: 60%
“…Fourth, the preoperative staging of PDAC improved over time thereby increasingly determining treatment proposals in multidisciplinary conferences, ultimately evolving the concept of multimodal neoadjuvant therapy for borderline resectable PDAC with considerable oncological benefit. 25 Given the fact that evaluation of patients with PDAC varies between different interdisciplinary conferences, 47 resection criteria for PDAC should be defined more precisely. Because the outcome of the so-called biological borderline group (preoperative CA 19-9 serum levels [ 500 U/ml) is so poor, new neoadjuvant regimens, including FOLFIRINOX, should be evaluated in randomized clinicals trials in this cohort of patients.…”
Section: Discussionmentioning
confidence: 99%
“…They found that MDT treatment decisions were based on group consensus (92%), adherence to clinical practice guidelines (57%), or other evidence-based medicine sources (33%) [46]. Kirkegård et al showed a high heterogeneity in the staging of pancreatic tumors and in the definition of resectability between European MDTs [47]. Similar variability is to be expected between head and neck MDTs.…”
Section: Multidisciplinary Teams Integrated Carementioning
confidence: 97%